Mildred Tie Ten Quee ([Kingston, Jamaica] : Planters' Punch, 1930)
Miss Mildred Tie Ten Quee, who will study medicine on leaving school, [1930]
Keywords: Tie Ten Quee, Mildred; Chinese - Jamaica - History; Chinese - Jamaica